Effect of Life Skills Training Based on Effective Communication and Emotion Management on Marital Satisfaction, Hopefulness and Self-Confidence in Spouses of Spinal Cord Injured Veterans - S. Namavar; S. Ghodrati; Z. Gholami Heydarabadi (Afarand Scholarly Publishing Institute, 2019)
Aims: War causes physical and psychological problems for people who are directly and indirectly involved in the war, including spouses of veterans. The aim of this study was to investigate the effectiveness of life skills training, including emotion management and effective communication skills on marital satisfaction, hopefulness, and self-confidence in spouses of spinal cord injured veterans of Tehran.  Materials & Methods: This semi-experimental research with pre-test and post-test design and control group was carried out on 30 spouses of spinal cord injured veterans who were residents of Tehran in 2018 by convenience sampling. The subjects were classified into control and experimental groups (N=15). Data were collected through standard enrich marital satisfaction, Schneiderchr('39')s hopefulness, and Bernreuter personality questionnaires. The pre-test was implemented for each of the 30 subjects. Then, the experimental group received 12 sessions of intervention including 7 sessions of emotion management skills training and 5 sessions of effective communication training and the post-test was performed again. Data were analyzed by SPSS 22 software using the paired t-test. Findings: There was no significant difference between mean scores of hopefulness, self-confidence and marital satisfaction in control group in the pre-test and post-test step (p>0.05), however, the mean scores of these variables in the experimental group showed a significant increase in the post-test compared to the pre-test (p<0.05). Conclusion: Skill training of emotion management and effective communication are effective in enhancing marital satisfaction, hopefulness, and self-confidence of spouses of spinal cord injured veterans.